COMPANY VALUE IN KOMPAS 100 INDEX PERIOD 2017-2021: THE ROLE OF GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, AND FINANCIAL PERFORMANCE - Nursanti, Tinjung Desy; Ningsih, Fitria (Universitas Gunadarma, 2024)
The objective of this study is to investigate the impact of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), Enterprise Risk Management (ERM), and Financial Performance on Company Value. The samples included in this study comprised of companies that were listed in the KOMPAS100 index for the period spanning from 2017 to 2021. The sampling methodology employed in this study was the use of simple random sampling, resulting in a sample size of 40 companies. The employed analytical framework is multiple linear regression analysis, enabled by the application of SPSS software. The findings of this study indicate that the variables of GCG (Good Corporate Governance), CSR (Corporate Social Responsibility), ERM (Enterprise Risk Management), and Financial Performance collectively exert a substantial and favorable impact on the value of a company. To a certain extent, the variables of GCG (Good Corporate Governance) and Financial Performance exhibit a notable and favorable influence on the valuation of a company. Conversely, the factors of CSR (Corporate Social Responsibility) and ERM (Enterprise Risk Management) do not show a statistically significant impact on the magnitude of Company Value. Thus, investors may take into account the inclusion of data pertaining to a company's Good Corporate Governance (GCG) policies and Financial Performance when making investment choices. Company management must acknowledge the significance of implementing efficacious corporate governance processes and augmenting financial performance as strategic measures to enhance the value of the organization.